The Effect of Job Satisfaction on Employee Turnover Intention in Companies PT. Hadji Kalla Branch of Urip Sumoharjo - Hasbiah, Siti; Idris, Muhammad (PT. Maju Malaqbi Makkarana, 2023)
This study aims to analyze the effect of job satisfaction on turnover intention. The population in this study are employees who are at PT. Hadji Kalla Makassar, Urip Sumoharjo Branch, with a total sample of 51 employees. This research is a quantitative study and quantitative analysis, using a simple regression test model using the SPSS version 25 software. The results of this study indicate that job satisfaction has a negative and significant effect on turnover intention with a correlation coefficient value of 32.5%